Timing and other factors influencing shortterm outcomes of endoscopic transpapillary gallbladder drainage for acute cholecystitis: a retrospective study - Fumitaka Niiya; Naoki Tamai; Masataka Yamawaki; Jun Noda; Tetsushi Azami; Yuichi Takano; Fumiya Nishimoto; Masatsugu Nagahama (BMC Gastroenterology)
Abstract Background Endoscopic transpapillary gallbladder drainage (ETGBD) is used to manage acute cholecystitis (AC) in patients in whom surgery is contraindicated. However, ETGBD is considered challenging, has comparatively lower success rates, and is associated with severe adverse events (AEs). Only a few studies have examined the procedural and anatomical factors that affect the success of technical ETGBD. This study identified predictive factors for ETGBD in AC to improve success rates and minimize AEs. Methods Patients treated with ETGBD for AC were assessed. Factors associated with technical failure were analyzed based on the interval from symptom onset to ETGBD, the presence of cystic duct stones, and cystic duct diameter. Results Among 68 patients, the technical success and AE rates were 64.7% and 19.1%, respectively (cystic duct perforation, 8.8%; pancreatitis, 5.9%). Multivariate analysis revealed that early ETGBD and stone impaction in the cystic duct were significantly associated with technical ETGBD failure. Subgroup analysis demonstrated that early ETGBD was associated with a significantly higher risk of cystic duct perforation and a lower success rate than elective interventions. Thus, elective ETGBD may enhance procedural success and reduce the risk of cystic duct perforations. Conclusion Elective ETGBD may be considered in cases in which ETGBD is anticipated to be challenging.